Synthesis and characterization of calcium carbonate obtained from green mussel and crab shells as a biomaterials candidate - Ismail, Rifky; Cionita, Tezara; Wong, Ling Shing; Fitriyana, Deni Fajar; Siregar, Januar Parlaungan; Bayuseno, Athanasius Priharyoto; Nugraha, Fariz Wisda; Muhamadin, Rilo Chandra; Ramli, Junid; Nor Azam, Endot (MDPI, 2022)
Green mussel and crab shells are natural sources of CaCO3, which is widely used as a bioceramic for biomedical applications, although they are commonly disposed of in landfills. The improper disposal of green mussel and crab shells can cause environmental pollution, reducing the quality of life in the community. Many studies have reported the preparation of CaCO3 from green mussels and crab shells. However, there are limited studies comparing the characteristics, including the crystal phase obtained, weight percentage (%) of crystal, crystal size, crystal system, and elemental composition of CaCO3 from green mussel shells, crab shells, and commercial CaCO3. The objective of this research was to compare the calcium carbonate properties formed from green mussel (PMS) and crab (PCS) shells to commercial CaCO3. Green mussel and crab shells were crushed to powder and were calcined at 900 °C for 5 h. Precipitated Calcium Carbonate (PCC) was synthesized from calcined green mussel and crab shells using a solution of 2M HNO3, NH4OH, and CO2 gas. The effect of setting parameters on the synthesized product was analyzed using XRD and SEM-EDX methods. This study shows that the chemical composition of PMS is nearly identical to that of commercial CaCO3, where no contaminants were identified. In contrast, PCS has N components other than Ca, C, and O. Furthermore, the predominance of the vaterite crystal phases in PMS and PCS, with respective weight percentages of 91.2% and 98.9%, provides a benefit for biomaterial applications. The crystallite sizes of vaterite in PMS, PCS, and calcite in commercial CaCO3 are 34 nm, 21 nm, and 15 nm, respectively.